An Update on Mitophagy Facilitating Substances: Their Future for Facilitating Healthy Ageing Along with Treating NDG (Parkinson’s Disease; Alzheimer’s Disease), Cancer, Ovarian Ageing: A Mini Narrative Review - Kaur, Kulvinder Kochar; Allahbadia, Gautam Nand K; Singh, Mandeep (British Journal of Healthcare and Medical Research, 2024)
The elimination of injured mitochondrial constituents via an event called mitochondrial autophagy (alias mitophagy) is necessary for appropriate mitochondrial working, thereby mitophagy is crucial for the health of all the aerobic animals inclusive of humans. To our misfortune reduction of mitophagy takes place with age. A plethora of age-related diseases for instance Alzheimer’s disease, along with Parkinson’s diseases have the properties of accrual of injured mitochondria in addition to oxidative injury. Thereby utilizing small molecule pharmacolological agents, for activating mitophagy is an upcoming approach the treatment of myriad of diseases. Recent studies have isolated natural agents, as well as synthetic agents which facilitate mitophagy. Categorization of such substances have been done in the form of mitophagy stimulators inclusive of i) antioxidants ii)) mitochondrial uncouplers iii) complex I hampering agents iv) redox manipulators v) metabolic manipulators vi) neuronal manipulators vi) autophagy manipulators vii) antibiotics along with anti-fungal agents viii) reactive oxygen species (ROS) producers. Their influence on stimulating the prolongation of life- along with health span in addition to mechanistic modes is further illustrated if acknowledged. Lastly, mitochondrial bio generation leads to harmony amongst mitophagy for guaranteeing appropriate mitochondrial network homeostasis. Intriguingly, mitochondrial biogeneration activation might be caused by akin molecules stimulating mitophagy for instance, resveratrol in addition to metformin. Although remarkable work has been undertaken regarding acquisition of insight regarding such events, plethora of information needs unraveling, specifically in the context of acquisition of insight of their interassociation at the level of organism along with evaluation of combination of such agents which target mitophagy as well as biogeneration. Future asssessment of such field might be unveiling the manner such combinations might be influencing lifespan along with health span in different biological models.